Difficulties facing the Management of Technological Change in School Libraries from the Schools' Librarian point of view in Lattakia City - Afield Study - جبلاوي, رنيم (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The research aimed to identify the difficulties facing the management of technological change in school libraries from the schools' librarian point of view in Lattakia city, and to identify the difference in their opinion according to variables (scientific qualification and years of experience).The research used the descriptive approach, and used a questionnaire has been included (48) items, included five fields: Difficulties (strategic, technological, human and financial, administrative, organizational) also studied their psychometric properties, and formed the sample of (118) Librarian, in first Cycle of Basic Education Schools in Lattakia city for the academic year 2020/2021. The researcher reached several results, the most important of which is: The difficulties of the facing the Management of Technological Change in School Libraries from the Schools' Librarian point of view in Lattakia City came to a high degree. There are statistically significant differences regarding with the difficulties facing the management of technological change in school libraries from the schools' librarian point of view in Lattakia city according to variable educational qualification in favor of the Education Preparation Diploma, No statistically significant differences regarding with the difficulties facing the management of technological change in school libraries from the schools' librarian point of view in Lattakia city according to variable experience.